Fiscal Discipline in the Euro Area Inder Conditions of the Financial Crisis - Spychała , Joanna (Studia Oeconomica Posnaniensia, 2014)
The aim of this article is to present, compare and evaluate the changing regulatory and legal arrangements under which disciplined fiscal policy is conducted in the Economic and Monetary Union (EMU). Particular attention is focused on fiscal discipline during the recent financial crisis. The crisis has confirmed the fact that effective fiscal and economic surveillance is a cornerstone for the smooth functioning of the EMU. The excessive deficit procedure has been subjected to detailed analysis, along with the current scope of its application in the individual Eurozone countries.